Do sacrifício ao mérito : estudo sobre o significado da doação para o fiel Iurdiano - Silva, Rosane Guedes da (2011)
The debates about the increasing of Pentecostal religious scene in Brazil have been constant among the social sciences. For them, this is considered as an indicator for its development, the spread of prosperity theology, based on the methodical construction of a single religious path that leads the individual to reach their personal achievements. Inside this religious model stands nowadays, the Igreja Universal do Reino de Deus (IURD). A research object in many areas of the human sciences, this institution presents itself today surrounded by numerous academic criticisms in particular in what regards its methods of raising finances, being interpreted in some studies as a large company of salvation. These considerations are developed from the emphasis on religious contributions to the Igreja Universal, translated here in the form of donations, which are seen as pillars in the religious experience of the individual, defining someone as a promising successful person. Thus, setting from the current socioanthropological studies on religion and contemporary society, and entering with this paper through the debate between religion and modernity. Trying to approach the connexion between the religion and the social experiences of people involved, and studying the symbolic meaning of religious donation to the participants directly involved in the donation process. Situating the relevancy of gift and counter gift through the process of content assimilation about the meaning of self-giving and sacrifice to achieve the desired and discussing these actions on the daily lives of these characters. So, this paper seeks to consider how the practice of ritual sacrifice of religious donations interferes in the construction of the social behavior of neo-Pentecostal iurdianos.